The Effect Of Financial Inclusion On Umkm Performance (Case Study Of Kota Pari Village) - Hernawaty; Heriyati Chrisna; Sri Wahyuni; Patwa Nirmala (International Journal of Management, Economic and Accounting, 2024)
The purpose of the study is to analyze the influence of financial inclusion on the performance of MSMEs in Kota Pari Village which has good enough potential to develop. Micro, small, and medium enterprises (MSMEs) contribute to reducing unemployment, poverty, equitable development and community income. However, MSMEs also experience obstacles in the development process. One of the common problems faced is the limitations of working capital, technology, production, marketing and business operations, and the quality of human resources. This will have an impact on performance if economic entities cannot manage their finances properly. To improve the performance of MSMEs, loan assistance from financial institutions is needed so that MSMEs can develop and be sustainable. Improving business financial management in order to facilitate loan repayment and develop the capital owned in order to take advantage of existing opportunities and increase business turnover and profits. This effort will certainly be realized soon if the level of financial inclusion of MSMEs is high enough. The research sample is the owners and managers of MSMEs in Kota Pari Village as many as 80 respondents. This study uses a quantitative method. The data collection method uses a non-probability sampling technique using a questionnaire. The data analysis techniques used are descriptive analysis of percentages, instrumental tests, and hypothesis tests. The instrument test consists of a validity test and a reliability test. The hypothesis test consists of a simple regression, a partial test (t-test) and a partial determination coefficient (r2). Based on the results of the research that has been carried out, it is known that financial inclusion has an effect on the financial performance of MSMEs in Pari City, this is strengthened by the results of hypothesis tests obtained with a sig. 0.000 that is declared to have a positive effect.